Developing a fuzzy inference system to devise proper business strategies: A study on carpet industry - Nasrin Hemayatkar; Kaveh Khalili-Damghani; Hosein Didehkhani; Roohalla Samiee (Journal of Industrial Engineering International, 2019)
The present article formulates the scenarios that the organization will be probably facing with, using the uncertain factors in business environment, and it also selects the most robust strategies of organization for dealing with the formulated scenarios using the fuzzy information expressed by the experts in fuzzy inference system. The present article aims to provide a method enabling the scenario programmers to employ robustness philosophy using the scenario planning potentials and fuzzy inference system at the decision-making stage of the general process of strategy formulation. The process helps the strategic managers of the organizations to determine their business future clearly and enables them to select their robust scenario in the current market that is uncertain. After the introduction of the robust strategic planning methodology and illustrating its different stages, the selected strategies of them will be compared at the end of the article by implementing the strategic planning method in a practical case. The results of the research have been examined as a case study for carpet industry.
Keywords: 650; Fuzzy inference system; Robust scenario planning; Strategic management; Success factors of organization